From bench to small notebook: Discretion and stigma in enrollment procedures in cariocas´s schools - Oliveira, Ryna Wanzeler de (2022)
The article analyzes the enrollment procedures of municipal schools in Rio de Janeiro. We consider that Regional Education Coordination (CRE) and school are the bureaucrats responsible for implementing the enrollment policy and may act in a discretionary way. We consider that their perceptions about schools, students and parents are based on stigmas. We used interviews carried out with regional staff and with school directors. The results show the bureaucracy's discretion in enrollment procedures and reveal the production and reproduction of stigmas in schools, reinforcing a scenario of educational inequality and a tendency towards inequity in the distribution of places.